Studi Kasus Serta Perawatan pada Kompressor di PT Sakura Java Indonesia - Herdianto, Muhammad Ihza; Gusniar, Iwan Nugraha; Santosa, Aa (Universitas Batanghari Jambi, 2024)
Quality products, quality production processes are very important, from materials to products; However, problems and obstacles may develop in the production process. The aim of this research is to find out the problems that arise in the manufacturing process and find problems with the compressor which has an oil filter leak so that the air pressure consumed in the production process is reduced. FMEA is an organized approach to identifying and avoiding as many failure scenarios as possible. Data is processed by calculating the Risk Priority Number value in FMEA and determining the criticality of each failure mode. The assessment is based on the results of rounding the average weighting value for severity, occurrence and detection levels. The results of calculations using the FMEA technique show that the oil filter leak due to a broken ring creates a Risk Priority Number (RPN) value of 90. Overcoming the problem of oil filter leaks due to a broken ring requires preventive maintenance for 5000 hours.